Pengembangan Desa Wisata Melalui Pemberdayaan Masyarakat Desa Celuk, Sukawati, Gianyar - Prabasari, Ni Putu Yulinda; Suka Arjawa, I Gst. Putu Bagus; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
The development of tourist villages through community empowerment is one alternative in planning a tourist attraction by prioritizing local potential in opening up greater opportunities both in terms of social and economic activities in the tourism sector. The theory used in this research is the theory of community empowerment from Jim Ife and Frank Tesoriero with three community empowerment strategies. The research method used is a qualitative research method. The results of this research are the tourism village development strategy in Celuk Village caused by interactions in the tourism sector. The tourism village development strategy through community empowerment provides benefits for tourism in Celuk Village, but these benefits have not been maximized due to external factors, namely the Covid-19 pandemic which has limited activities from both the economic and tourism sectors. Keywords: Strategy, Community Empowerment, Tourism Village Development, Celuk Village